Penguatan karakter siswa melalui pembelajaran pendidikan pancasila dan kewarganegaraan di sekolah dasar islam - Keysha Lingga Auli; Zenix Icha Ramadhani; Denis Denis Kholifatul Jannah; Sangcaesar Guido Permadinata (Prosiding Konferensi Ilmiah Dasar, 2026)
Pancasila Education plays a fundamental role in developing students' character as preparation for responsible citizenship and social life. This study aimed to describe the implementation of Pancasila Education in strengthening students' character at SD Islam Unggulan Sahabat Madiun. A descriptive qualitative approach with a document study method was employed. Data were collected from school documents, including teaching modules, instructional plans, school habituation programs, and character assessment records. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that character values were integrated into lesson planning, classroom learning activities, school habituation programs, and character assessment. The implementation was supported by a religious school culture, teachers' exemplary behavior, principals' support, and collaboration between the school and parents. However, differences in students' characteristics, family backgrounds, the influence of digital media, and limited instructional time remained challenges. The study concludes that an integrated implementation of Pancasila Education contributes to sustainable character development among elementary school students.